A Brief Chronicle of the Genus Cordyceps Fr., the Oldest Valid Genus in Cordycipitaceae (Hypocreales, Ascomycota) - Shrestha, Bhushan (The Korean Society of Mycology, 2014)
The earliest pre-Linnaean fungal genera are briefly discussed here with special emphasis on the nomenclatural connection with the genus Cordyceps Fr. Since its valid publication under the basidiomycetous genus Clavaria Vaill. ex L. (Clavaria militaris L. Sp. Pl. 2:1182, 1753), the genus Cordyceps has undergone nomenclatural changes in the post-Linnaean era, but has stood firmly for approximately 200 years. Synonyms of Cordyceps were collected from different literature sources and analyzed based on the species they represent. True synonyms of Cordyceps Fr. were defined as genera that represented species of Cordyceps Fr. emend. G. H. Sung, J. M. Sung, Hywel-Jones & Spatafora. The most common synonyms of Cordyceps observed were Clavaria and Sphaeria Hall, reported in the 18th and in the first half of the 19th century, respectively. Cordyceps, the oldest genus in the Cordyceps s. s. clade of Cordycipitaceae, is the most preferred name under the "One Fungus = One Name" principle on priority bases.